Determining the Effects of Land Consolidation on Fuel Consumption and Carbon Dioxide Emissions in Rural Area - Havva Polat; İsmail Manavbaşı (Journal of Agricultural Sciences, 2012)
Expected achievement of land consolidation depends on the priority given to the protection of water, soil and air quality which are the elements of rural environmental balance. Today, many of researches have carried out to determine the effects of land consolidation on the local hydrology and agricultural productivity. However in this study impact of land consolidation projects on air quality of rural environment have been tried to determine. Total of 20 enterprises were selected including four projects and five enterprises chosen according to multipurpose sampling method from each projects for the study. Projects and enterprises selected for research differ from each other as parameters of topography, the number of enterprises, distribution of parcels and village centres on project area, the length of path between parcels and farmyard centre, number of parcels. As a result of land consolidation projects applications, effects of changes in path length and routes on fuel consumption of tractors and also the carbon dioxide (CO2) emission values are tried to determine in these areas. In order to identify changes in road lengths, before and after land consolidation’s maps, data obtained from land studies and satellite images about selected projects are used. It is calculated that path length of farmer’s daily go and back between farm centre and parcels shortened about average 26.68 km (at least 6.44 km and up to 70.24 km) after land consolidation in research areas. Shortening of path length reduced the fuel consumption to average 10.86 L (at least 2.62 L and up to 28.59 L), and carbon dioxide (CO2) emission decreased to average 28.93 kg (at least 6.98 kg and up to 76.16 kg). It’simportant to know the carbon equivalent value corresponding carbon dioxide emissions for measurement of greenhouses gases emissions’ effects on global warming. Carbon equivalent values’ (CE) reduces were calculated for per kilometre as at least 1.90 kg and up to 20.77 kg and average 7.89 kg for the research. Fuel consumption was saved 48.8 L ha-1 in farm and crop production activities after land consolidation for one crop production period. In addition to having advantages for increasing the agricultural production and productivity, land consolidation projects have contributed to protection of air quality in rural areas. Especially having been reduced fuel consumption and carbon emissions partly prevents from air pollution and the adverse effects of climate change.